"CHRONIC SORROW THEORY APPLICATION" TO OVERCOME THE FEELING OF LOSS DUE TO INFANT MORTALITY IN POST-PARTUM WOMEN - Dedeh Sri Rahayu (Journal of Maternity Care and Reproductive Health, 2019)
Data from the World Health Organization (WHO) in 2012 stated that 44% of infant deaths in the world occurred in the first 28 days of life (neonatal period). The research results of the Central Statistics Agency (CSA) in 2016 noted that the infant mortality rate (IMR) reached 25.5%, West Java Province was one of the contributors to the highest maternal mortality rate (MMR) and infant mortality rate (IMR). Infant mortality inside the womb or outside the womb triggers grief and deep sorrow that is at risk of progressive, repetitive and permanent in women. Nurses in the maternity area play an important role in overcoming the problem of loss through various approaches to either theory or intervention. The purpose of this study was to determine the application of chronic sorrow theory in post-partum women whose babies were dead at Sariningsih Hospital Bandung. Method: This research was qualitative research. Participants were 5 people selected using purposive sampling techniques. Data collection was done by interviewing using a guide from the Burke / Eakes Chronic Sorrow Assessment Tool. Results: It was identified that women's opinions about the causes of infant mortalities were planned (abortion) and unplanned. Participants had effective coping strategies in dealing with their loss such as social support, and spiritual beliefs for comfort. Conclusion: participants felt the effectiveness of the chronic sorrow theory to overcome infant loss.Keywords: chronic sorrow theory application, loss, post-partum women, Qualitative.